Kajian Teoritis tentang Problem Based Learning dan Kemampuan Berpikir Kritis terhadap Hasil Belajar Fiqih - Rohmah, Mar-Atin Nabila; Subando, Joko (TSAQOFAH, 2026)
Fiqh instruction in madrasahs plays a strategic role in shaping students’ understanding of Islamic law as applied in everyday life; however, classroom practice still faces challenges, including low student participation and underdeveloped critical thinking skills due to the dominance of conventional instructional models. This article aimed to theoretically examine the influence of the Problem Based Learning (PBL) model and critical thinking skills on students’ learning outcomes in Fiqh. The study employed a qualitative approach with a library research design, drawing data from a review of books, scholarly journals, and previous studies relevant to PBL, critical thinking, and learning outcomes. The review indicates that PBL can create student-centered learning, promote active engagement, and develop critical thinking through contextual problem solving. Critical thinking functions as an internal factor that strengthens students’ understanding of Fiqh material, particularly in analyzing Islamic legal issues and differences of scholarly opinion. Theoretically, the synergy between implementing PBL and strengthening critical thinking skills contributes positively to improving students’ learning outcomes in Fiqh and provides a conceptual basis for transforming instruction in madrasahs toward more active and reflective learning. Accordingly, this review offers an important theoretical foundation for subsequent empirical research on Fiqh learning and the development of problem-based instructional models in Islamic education.